Omejevanje avtonomije pogodbenih strank kot dejavnik zagotavljanja delovnopravnega varstva - Tičar, Luka (Delavci in delodajalci, 2009)
The contribution deals with the phenomenon of the autonomy of the contracting parties in labour law. At the beginning author argues different meaning and content of autonomy in civil and labour law accepting labour law as an independent legal branch with its special legal nature and unique role in a society. Afterwards author predominantly deals with limitation of employer's autonomy, which he sees as the key factor of labour protection assurance. Limitation of employer's autonomy is represented threw some specific labour law institutes or some fields of employer's acts before or during employment relationship.
Keywords: delovna razmerja; delovne pogodbe; delovno pravo; pogodba o zaposlitvi